Quantitative health risk assessment of microbial hazards from water sources for community and self-supply drinking water systems - Yan, Cheng; Wan, Wei-di; Wang, Rui-ning; Lai, Tian-nuo; Ali, Wajid; He, Shan-shan; Liu, Sai; Nasir, Zaheer A.; Coulon, Frederic (Elsevier, 2024)
In low and medium income countries (LMIC) drinking water sources (wells and boreholes) often contain a high number of pathogenic microorganisms, that can pose significant human and environmental health risks. In this study, a quantitative microbial risk assessment approach based on existing literature was conducted to evaluate and compare the quantitative health risks associated with different age groups using various drinking water supply systems. Results showed that both community-supply and self-supply modes exhibit similar levels of risk. However, the self-supply water source consistently showed higher risks compared to the community-supply one. Borehole water was found to be a more suitable option than well water, consistently showing between 5 and 8 lower health risks for E. coli and fecal coliform levels, respectively. The sensitivity analysis further showed the importance of prioritizing the reduction of E. coli concentration in well water and fecal coliform concentration in borehole water. This study offers a fresh perception on quantifying the impact of exposure concentration and age groups, shedding light on how they affect environmental health risks. These findings provide valuable insights for stakeholders involved in the management and protection of water sources.
Keywords: Quantitative microbial risk assessment; Drinking water; Well and borehole water; Drinking water supply systems; Sensitivity analysis